2022
DOI: 10.4414/smw.2022.w30195
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective data analysis for definition of multidrug resistance in gram-negative bacteria – a consensus proposal

Abstract: AIM OF THE STUDY: The main objective of this study was to propose a common definition of multidrug-resistant gram-negative organisms (GN-MDRO), which may be used for epidemiological surveillance and benchmarking. METHODS: In this retrospective data analysis, we used interpreted qualitative susceptibility data (SIR) from blood culture isolates of different gram-negative microorganisms from the ANRESIS database from 2017–2021. We first analysed testing algorithms used by different Swiss laboratories and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several definitions of MDRO have been proposed, some of which are limited to GNB [ 23 , 24 ]. We used the criteria proposed by the ECDC, accounting for GNB and GPC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several definitions of MDRO have been proposed, some of which are limited to GNB [ 23 , 24 ]. We used the criteria proposed by the ECDC, accounting for GNB and GPC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies comparing MDRO definitions reported high variability of the resistance rates, with the ECDC definitions being associated with the highest rates of resistance [ 24 ]. The ECDC definitions have been criticized as they encompass resistance to many antibiotic families, including those rarely used in IAIs such as monobactams, non-beta-lactam cell wall synthesis inhibitors, protein synthesis inhibitors or antifolate agents [ 23 , 24 ]. This issue led us to broaden our analysis and to assess the changes in adequacy of EAT and the best theoretical treatments over the study period.…”
Section: Discussionmentioning
confidence: 99%